Continuity and Change in Labour Relations: Facing Facts - Goldenberg, H. Carl (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
Continuity implies the existence of certain basic facts which must be faced when we think in terms of change because change in the area of labour-management relations cannot be effected in a vacuum. And the basic fact is that labour-management relations are human relations, that basic to the conduct of labour relations and the avoidance of industrial disputes is an appreciation of underlying human fact ors.